Developing economies and environmental impact: A VECM analysis of external debt, ODA, and CO2 - Mazher, Muhammad Ahmad; Tramankuti, Yasotha Nair; Osman, Zurul Aisya (YAYASAN MITRA PERSADA NUSANTARA, 2023)
The objective of this study is to examine the carbon dioxide (CO2) emissions in Asian economies between 1990 and 2019, with a specific focus on their relationship with net official development assistance (NODA) and external debt. Utilizing the IPAT model as a theoretical framework, we employ various econometric methodologies to estimate both long-term and short-term outcomes. These methodologies encompass panel unit-root tests, cointegration techniques, and the VECM method. The findings of the research provide additional substantiation for the presence of cointegration among all variables. The analysis of long-term data revealed a robust and statistically significant relationship between gross domestic product (GDP) and carbon dioxide (CO2) emissions. Conversely, a strong and inverse connection was identified between foreign debt and net official development assistance (NODA). The results indicated a modest but favorable relationship between the size of the Asian population and the levels of CO2 emissions. The segment of recommendations encompasses comprehensive proposals and an extensive examination of various alternatives.